Prevalence of Premenstrual Syndrome among Medical Students - Akbari M, Rumana; Sudharani, M; Kallupurackal, Sherin Joseph Xavier; Ramya, V; Gowda M R, Nagendra; Suryakantha, A H (National Journal of Community Medicine, 2017)
Introduction: Premenstrual syndrome (PMS) is the name given to a collection of physical and psychological symptoms that most women experience during the late luteal phase of each menstrual cycle , the symptoms of which fall into three domains: emotional, physical and behavioral. These symptoms may be of such severity that they can disrupt interpersonal relations, social activities, work performance or quality of life. Women are affected irrespective of socioeconomic status, race or cultural background. Objectives: The study was conducted to know the prevalence of PMS and to study the factors associated with PMS among medical students. Methodology: A cross sectional study was conducted among 270 medical students of Basaveshwara medical college, Chitradurga. Self-evaluating questionnaire covering socio-demographic factors like age, place of residence, weight, height and questions on PMS were analyzed.Data was analysed using SPSS version 20. Results: The prevalence of PMS among the study participants was 31.1 %, among them 20%,7.4% ,3.7%,0% showed mild, moderate, severe and very severe form respecctively. BMI, Place of residence, year of MBBS and age of menarche were the factors significantly associated with premenstrual symptoms. Conclusion: The prevalence of premenstrual syndrome is high among college students and it is increased increasing age.Premenstrual symptoms can be managed if diagnosed in right time with suitable pharmacological and non-pharmacological aids.